Little Caesar - Faragoh, Francis Edward 1895-1966; Robinson, Edward G. 1893-1973; Fairbanks, Douglas 1909-2000 (Turner Entertainment Co., 2014)
Small-town criminals Caesar "Rico" Bandello (Edward G. Robinson) and Joe Massara (Douglas Fairbanks Jr.) move to Chicago to hit the big time. While Rico makes a name for himself in the underworld, Joe decides to leave the life of crime and ventures into show business, where he meets the lovely dancer Olga (Glenda Farrell). Though Rico and Joe try to honor their friendship, eventually their choices take them down different paths
Original USA 1930
Bildformat 1.37:1
Cover: "Special features: commentary by Richard Jewell ; Warner Night at the Movies ; Little Caesar: end of Rico, beginning of the antihero ; re-release forward ; theatrical trailer"
Keywords: Gangsters / Illinois / Chicago / Drama; Prohibition / Illinois / Chicago / Drama; Gangsters; Prohibition; Illinois / Chicago; Gangster films; Crime films; Film noir; Feature films; Fiction films; Film adaptations; Video recordings for the hearing impaired; Drama; Film; DVD-Video